Association of Human Papillomavirus Vaccination with Risk for Rheumatoid Arthritis - Yen-Tze Liu; Yung-Heng Lee; An-Ping Huo; Shiow-Ing Wang; Chih-Cheng Lu; James Cheng-chung Wei (Journal of Clinical Rheumatology and Immunology)
Introduction: The potential association between Human papillomavirus (HPV) vaccination and the onset of rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) remains a pivotal point of exploration in immunization safety discourse. Method: This retrospective cohort study aims to ascertain the risk of RA and JIA following HPV vaccination, utilizing the TriNetX database, tracking the health trajectories of 32,165,650 females, from January 1, 2013, to December 31, 2022. By applying inclusion and exclusion criteria, we formed a balanced cohort of 344,165 HPV-vaccinated individuals, the propensity score-matched 1:1 with unvaccinated controls based on a range of demographic and clinical parameters. This study used the Cox proportional hazards model to analyze the risk of RA and JIA after HPV vaccination, expressed the results by adjusted hazard ratio (aHR) and 95% confidence interval (CI), and used Kaplan-Meier survival analysis. Results: The analysis showed that over a follow-up period of up to 10 years after vaccination, the risks of RA and JIA were significantly reduced in the HPV vaccination group, with aHR of 0.428 (95% CI: 0.372-0.492) and 0.310 (95% CI: 0.262-0.367) respectively. This trend persisted in a sensitivity analysis that replaced the control group with influenza-vaccinated individuals. Subgroup analyses showed that the risk of RA and JIA was significantly reduced in the 9-18 and 19-26 age groups, across ethnic backgrounds, and in the obesity and asthma subgroups, but still among those with a smoking history, the risk reduction was not statistically significant. Conclusion: Our findings highlight the significant protective effect of the HPV vaccine against RA and JIA. Further research is needed to delve deeper into this molecular mechanism.